PENERAPAN TEKNOLOGI PAKAN TERNAK DAN PENGOLAHAN LIMBAH PETERNAKAN DI DESA OELTUA KABUPATEN KUPANG - Catootjie L. Nalle; Marlin R.K. Yowi (Jurusan Peternakan Politeknik Pertanian Negeri Kupang, 2016)
The long term objective of this activity is to improve the income of farmers (partner) in Dusun Binilaka, Oeltua Village, Kecamatan Taebenu District, Kupang Regency, East Nusa Tenggara. The special target is to improve the production performance of pigs and cows of farmers the implementation of feed technology, housing by product processing. Method used is survay, extension, and plot demonstration. This activity is expected to contribute to the implementation of feed technology to improve animal performance and to solve feed shortage in dry season in and to reduce feed cost.Â Key words: income, feed technology, housing by product, pigs, cows